The Testing of Selected Characteristics of Research Tools by way of Determining the Affective Dimension of Environmental Literacy of Second Graders at Primary School - Svobodová, Silvie (Scientia in educatione, 2020)
The affective dimension of environmental literacy represents the component that has been the most important attention in the last years in the field of environmental literacy testing both abroad and in our country. The most widely used tools are NEP (New Environmental Paradigm), 2-MEV (2 Major Environmental Values), NRS (Nature relatedness scale), and MSELS (Middle School Environmental Literacy Survey). The study presents the results of testing these instruments. It describes their psychometric properties, reliability and validity, and analyzes the impact of demographic variables (gender, age, age, size of residence) on environmental attitudes of of 12–15 years old pupils. The target group were 12–15 years old pupils across the Czech Republic. The reliability and validity of all instruments has been proven. The Cronbach alpha coefficient reached acceptable values (α> 0.7). Content and construct validity was discussed in the context of a number of previously published research. In the case of MSELS, the construct validity was confirmed separately, and for the remaining instruments, simultaneous criterion validity. Analysis of the impact of variables has brought contradictory findings. The relation of individual variables to the degree of affective dimension was significant only in some of them, especially in the 2-MEV and MSELS. Based on the results, it can be stated that these are unstable factors in relation to the affective dimension of environmental literacy of 12–15 years old pupils. Tested tools, however, can be recommended to measure the construct for a given target group.